Frequency of Left Atrial Thrombus Among Patients with Mitral Stenosis Undergoing Percutaneous Trans-Septal Mitral Commissurotomy - Khan, Asfandiyar; Iqbal, Muhammad Asif; Fahad, Usama; Roohulamin; Sohail, Muhammad; Ali, Hassan (Indus Journal of Bioscience Research, 2025)
Mitral stenosis (MS), most commonly resulting from rheumatic heart disease, predisposes to left atrial thrombus (LAT) formation due to atrial enlargement, stasis of blood flow, and structural remodeling. LAT poses a major risk of systemic embolization and directly influences procedural planning for percutaneous trans-septal mitral commissurotomy (PTMC). This cross-sectional study was carried out in Department of Cardiology, Lady Reading Hospital, Peshawar, between 24 October 2024 and 24 April 2025 to find out the frequency of LAT and related factors in patients under grass root surgery PTMC. Consecutive non-probability sampling was conducted among 133 patients with age 1870 years with symptomatic MS. Baseline demographic and clinical information such as comorbidities, anthropometric measurements, were noted. All the subjects were subjected to prep r o c e d u r a l transesophageal echocardiography to identify LAT. Data analysis was performed with SPSS version 21 with Stratified analysis used to evaluate relationships between LAT and possible effect modifiers. The average age of the cohort was 45.6 11.8 years in total, with the largest proportion of females (62.4%). The occurrence of LAT was found in 13 individuals (9.8%). Prevalence of LAT was significantly correlated to hypertension (p = 0.03) and BMI >25kg/m 2 (p = 0.04) with no significant correlation with either gender, residence, diabetes or smoking history. These findings stress the importance of extensive pre-procedural screening and mention among modifiable risk factors that can lead to thrombus in patients with MS. Clinicians can streamline procedural safety by means of identifying high risk subsets to minimize embolic complications during PTMC. More research is necessary to determine whether the long-term effects of modifying risk factors influence the prevalence and clinical outcome of LAT in the population.